Opportunities from the social economy in the fight against the threats of AI - Miguel Guillén Burguillos; Eloi Serrano Robles (Revista CIDOB d'Afers Internacionals)
Social economy enterprises cannot shun artificial intelligence (AI) as it is useful for performing miscellaneous business tasks. The key is to use it in a manner that is consistent with the principles of the social economy and to promote the development of an AI based on its values, placing people at the centre of the economic activity. The social economy can play an important role in democratising AI, because it carries out its activities while upholding principles such as ethics, justice, democratic management, equity, sustainability and the defence of people’s interests, their communities and societies, not just profits. This paper addresses the threats that current AI development may present and sets out the opportunities the social economy affords to ensure this development is based on more ethical and democratic criteria.